Subsegmentectomy versus segmentectomy resection for the treatment of operable patients with stage IA non-small cell lung cancer: A meta-analysis - Song, Liwei; Li, Shuping; Hao, Xuefeng; Jin, Renjing; Li, Wei; Zhang, Minghang; Wang, Jinghui; Zhou, Shijie; Ma, Teng; Xu, Shaofa (Frontiers in Surgery, 2023)
Background: There were new points of interest in performing subsegmentectomy and segmentectomy for patients with early stage non-small cell lung cancer (NSCLC). However, whether patients who underwent subsegmentectomy could obtain satisfactory clinical outcomes remains unclear. The present study aimed to compare the clinical outcomes and security of surgical procedures between subsegmentectomy and segmentectomy. Methods: A systematic review and meta-analysis was performed through five online databases to identify the included literatures which presented intact clinical outcome data among different surgical procedures. The included studies were evaluated based on precise and predefined inclusion criteria. Results: There were 4 published studies identified in this meta-analysis. A total of 325 patients who underwent subsegmentectomy and 904 patients who underwent segmentectomy were involved in this analysis. The duration of drainage [Mean Difference -0.19; 95%CI (-0.36, -0.02) p = 0.03] and postoperative hospital stay [Mean Difference -0.30; 95%CI (-0.58, -0.02) p = 0.009] of subsegmentectomy were significantly less than that of segmentectomy. There was no statistically significant difference among recurrence rate, operation time, blood loss, incidence of complications between subsegmentectomy and segmentectomy in patients with stage IA NSCLC. Conclusion: The meta-analysis was first performed to compare perioperative outcomes among surgical procedures. The clinical outcomes were comparable between subsegmentectomy and segmentectomy. Subsegmentectomy was considered an alternative treatment for deep tumor with size less than 1.5cm and mainly composed of Ground Glass Opacity (GGO). Keywords: non-small cell lung cancer, segmentectomy, subsegmentectomy, Meta-analysis, safety